Growth regimes in central and peripheral countries : an econometric analysis, 1980-2018 - López, Emiliano (Brazilian Journal of Political Economy.)
We explore structural differences in growth patterns and income distribution between central and peripheral countries. We provide dimensions that account for the structural limitations that dependent positions have in the peripheries and semi-peripheries. We conducted an analysis through different estimates of panel data models for 35 central and peripheral countries for the period 1980-2018. In particular, in addition to making the usual estimates of the components of aggregate demand, we include three variables that we consider representative of the dynamics that capital accumulation takes in the periphery: participation in global value chains, levels of foreignization of economies and labor productivity differentials.